IN VITRO EVALUATION OF THE IMPACT OF OPTICAL MAGNIFICATION ON THE PREPARATION FOR VENEERS - Aleksandra Pecheva; Snezhana Tsanova; Ralitsa Raycheva (Peytchinski Publishing, 2020)
Purpose: The preparation of hard dental tissues for veneers is а very technically demanding process, where minimal invasive manner matters. The optical magnification offers higher resolution; brighter and enlarged three-dimensional images which improve the precision and the working posture. The study is evaluating the impact of optical magnification on the precision of tooth preparation under simulated clinical conditions in а digital manner. Materials and Methods: For the test specimens, 60 plastic upper incisors are divided into 3 groups (n= 20): 1st group - teeth prepared with a naked human eye.; 2nd group - teeth prepared using compound loups x2,5 magnification; 3rd - teeth prepared using an operating microscope under x6.0 magnification. A laboratory scanning device is used to scan the teeth both before and after the preparation phase. Computer- aided design software is used to overlay the outlines of the teeth it all groups. A sagittal plane is constructed throughout the digital teeth images, and measurements of cut hard dental tissues are done in order to evaluate the accurateness of tooth preparation according to the depth of preparation. Results: There is a statistical difference between the pre-established volume of preparation and the actual cut of hard dentinal tissues no matter the magnification. There is a statistically significant difference between the depth of preparation in naked eye cases and the magnification cases. Conclusions: The quantity of cut tissues it more than the preestablished parameters which may affect the quality of the adhesive bond and it is controversy with the minimally invasive approach. The preparation under magnification is much more precise when compared to a naked eye.